Analysis of website-based village population administration system development methods: a review - AHSAN BAIHAQI (Borobudur Informatics Review, 2022)
The village population administration information system is a facility in a computerized system that has been equipped with features and is designed in such a way as to suit the needs to be used for inputting certain data which aims to simplify, speed up and accurate data that has been processed. The method used in conducting this systematic review uses concepts related to the village population administration system. Literature search is done through Google Scholar. The search was carried out in August 2021. The search was carried out using Indonesian. The research method is obtained from a literature study that searches for information in the form of references in journals. There are 10 journals that will be reviewed. Referring to the journal literature published from 2017-2021, the most widely used website-based village population administration information system development method is the waterfall method.